Physical exercise and chicken egg white supplementation increase muscle mass of stable COPD patients - Amin, Mona N.; Tarigan, Amira P.; Pradana, Andika; Ashar, Taufik; Osareniro, Osakue E. (Narra Sains Indonesia, 2024)
Patients with chronic obstructive pulmonary disease (COPD) commonly exhibit muscle atrophy and dysfunction due to a reduction in muscle mass; and protein supplements such as chicken egg whites have been reported to improve muscle mass. The aim of this study was to evaluate the impact of physical exercise and egg white supplementation on the muscle mass of COPD patients. An experimental study was conducted among stable COPD patients at Universitas Sumatra Utara Hospital Medan, Indonesia, between August and October 2022. The patients were divided into two groups, control and interventional groups, with each patient subjected to a pre- and post-muscle mass assessment. All the patients performed respiratory endurance and upper extremity muscle strength training three times/week for a total of 12 weeks. In addition, the patients in the intervention group were also given egg white supplementation (10 eggs/day) during the period of intervention in addition to the physical training. The Wilcoxon and Mann-Whitney tests were performed to identify the significance of the difference between pre- and post-intervention and between the control and intervention groups, respectively. A total of 38 COPD patients were included in the study, 19 from each group. Our data suggested no significant difference in muscle mass of the patients in the control group before and after 12 weeks of physical exercise (pre-intervention 27.37±4.54% and post-intervention 27.68±4.5% with p=0.174). However, there was a significant muscle mass increment of patients in the intervention group upon 12 weeks of physical training and egg white supplementation (pre-intervention 27.18±4.15%, post-intervention 29.95±3.76%, p<0.001). A significant difference in muscle mass was observed between patients in the control and the intervention groups (p=0.046) after the intervention. The study highlights that physical exercise in combination with egg white supplementation may serve as potential and effective non-pharmacological treatment for muscle mass restoration in COPD patients as compared to physical exercise alone.